Nomenclatorial changes in Triaenonychidae: Sclerobunus parvus Roewer is a junior synonym of Paranonychus brunneus (Banks), Mutusnonychus Suzuki is a junior synonym of Paranonychus Briggs, and Kaolinonychinae Suzuki is a junior synonym of Paranonychinae Briggs (Opiliones: Triaenonychidae) - Shear, William A.; Derkarabetian, Shahan (Zootaxa, 2008)
The harvestman species Sclerobunus parvus was described by Roewer (1931) from the Queen Charlotte Islands, British Columbia, Canada. Some forty years later, Briggs (1971) revised the Triaenonychidae of North America, but missed including Roewer’s species, which had not been mentioned in the literature since its description. Briggs (1971) recognized two subfamilies in North America, Triaenonychinae Sørensen 1886 (Briggs attributed the subfamily name to Pocock, but according to the International Code of Zoological Nomenclature, Sørensen’s original proposal of the family name included the nominate subfamily) and Paranonychinae Briggs 1971. Paranonychinae included two new genera, Metanonychus Briggs 1971 and Paranonychus Briggs 1971. The latter genus was based on Sclerobunus brunneus Banks 1893, a commonly occurring species distributed from Clackamas County, Oregon, north to Atka Island, Alaska (Briggs 1971).